The Effect of Culture of Use of Handphone on GPA of PAI Students at IAIN Takengon - Rosdiani Nasution; Evanirosa (Medan Resource Center, 2021)
Implementation of school-based management to improve the quality of early children education. The purpose of this study is to gain insight into the implementation of School Based Management (SBM) to improve the quality of education in Indonesia, especially Early Childhood Education (PAUD). This research is motivated by the importance of improving the quality of education in Indonesia to develop human resources and build national character and also to produce a smart and quality generation. The subject of the research was carried out at An-najah Integrated Islamic Kindergarten Takengon. The research method used is a qualitative descriptive approach by analyzing the facts in the field. The results showed that the implementation of School Based Management (SBM) in An-Najah Integrated Islamic Kindergarten was carried out through several management inputs which were then applied in the learning process and resulted in increased learning outcomes so that it could improve the quality of Early Childhood Education (PAUD).